1976
DOI: 10.1007/bf00016958
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soil compaction and nitrogen placement on weed population, yield and moisture use pattern of rainfed wheat

Abstract: Field experiments showed t h a t soil compaction did not affect wheat yield significantly under rainfed conditions. Weed population was significantly reduced due to soil compaction. Compaction decreased total moisture use and increased water use efficiency. There was better and profitable utilization of stored soil moisture from the compaction t r e a t m e n t s as compared to no compaction treatment.Placement of nitrogen about 10 to 15 cm deep in the soil directly below the seed resulted in significant incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…A deeper fertilizer placement may even improve crop growth over standard shallow or surface placements. Crop roots tend to proliferate around the area of the fertilizer grain, thus deeper placement can promote root length density and enhance N uptake (Lotfollahi et al 1997;Li et al 2009) as well as water utilization (Singh et al 1976) from deeper soil layers. Crops can obtain more than two thirds of their nutrition from deeper layers in the soil profile when nutrient availability and/or water is limited in the topsoil (Kautz et al 2013) and deep fertilization could improve plant growth, particularly during periods of little to no precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…A deeper fertilizer placement may even improve crop growth over standard shallow or surface placements. Crop roots tend to proliferate around the area of the fertilizer grain, thus deeper placement can promote root length density and enhance N uptake (Lotfollahi et al 1997;Li et al 2009) as well as water utilization (Singh et al 1976) from deeper soil layers. Crops can obtain more than two thirds of their nutrition from deeper layers in the soil profile when nutrient availability and/or water is limited in the topsoil (Kautz et al 2013) and deep fertilization could improve plant growth, particularly during periods of little to no precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly because after deep application of nitrogen fertilizer, NH 4 + -N is adsorbed by the soil as it diffuses in it, thereby reducing the NH 4 + -N concentration in the soil (Yao et al, 2018a). Deep application reduces contact between the fertilizer and air, promotes root length density (Singh et al, 1976), shortens the time taken for nutrients to move to the root system, increases the absorption and utilization of nitrogen by rice, ultimately reducing NH 3 loss in rice fields (Yao et al, 2018b;Drescher et al, 2021). In addition, Rychel et al (2020) and Qi et al (2012) found that increasing fertilizer placement depth may be an effective method for keeping plant available N over longer periods, and found that delaying the nitrogen fertilization period can reduce ammonia volatilization.…”
Section: Side-deep Fertilization and Fertilizer Utilization Efficienc...mentioning
confidence: 99%
“…Hefni et al (1983) [22] found that the number of grains spike -1 and ear length reduced significantly if irrigation would be stopped at tillering and booting stages of wheat. Wheat plant growth was poor and spike length was low at rain fed condition (Singh and Singh, 1996) [23] . The fertile spikelets spike -1 was increased significantly under four irrigation and six irrigation treatments than two irrigations (Naik et al, 1997) [24] .…”
Section: Effect Of Irrigation Regimes On Yield Characters and Yieldmentioning
confidence: 99%